Gender differences in trust and reciprocity: evidence from a large-scale experiment with heterogeneous subjects - Dittrich, Marcus (Applied economics, 2015)
This article examines gender differences in an experimental trust game. Recent studies have shown that men trust more and that women are more reciprocal in laboratory experiments. Participants in these studies, however, are typically university students who may not be representative of the entire population. In this study, we use data from a large-scale experiment with heterogeneous subjects who are representative of the German population. We find that men exhibit not only more trusting behaviour, but also more reciprocating behaviour than women. Moreover, our results are indicative of age-dependent gender differences. For men, we find an inverse U-shaped relationship between age, on the one hand, and both trust and reciprocity, on the other; however, we do not find age effects for women.